Cooperation Between Indonesia Battery Cooperation (IBC) and Hyundai on the EV Battery Project in Indonesia as A Form of Renewable Energy Solution in Response to Climate Change - Astuti, Widi; Putra, Ferdian Ahya Al (Jurnal Hubungan Internasional, 2024)
Energy frequently relates to bring up in relation to the Net Zero Emissions 2060 target. Finding a way to achieve zero carbon emissions with an energy sustainability solution in line with the seventeen Sustainable Development Goals (SDGs) is the goal. Indonesia and other nations follow the Energy Trilemma, which emphasized three primary factors—energy security, energy affordability, and sustainable energy—to become factors that are taken into account for planning and history in order to address all social, economic, and environmental aspects. More precisely, taking into consideration the capacities of both countries, South Korea and Indonesia have proposed several strategic alternatives, one of which is the EV battery project development strategy. In addition to resources and other forms of strategic support, South Korea invests in, owns, and controls technology for Indonesia. Indonesia is able to meet 52% of the world’s nickel demand. This study examines how the Hyundai consortia and the Indonesian Battery Corporation consortia worked together to build an EV battery project in Indonesia, which had an impact on both nations to achieve the solution of how to be one of the renewable energy solutions in response to climate change. Keywords: EV Battery; Trilemma Energy; Global Value Chain; Hyundai; IBC.